2019
DOI: 10.1002/ente.201800790
|View full text |Cite
|
Sign up to set email alerts
|

Freestanding 1D Hierarchical Porous Fe‐N‐Doped Carbon Nanofibers as Efficient Oxygen Reduction Catalysts for Zn–Air Batteries

Abstract: High‐performance nonprecious metal‐doped 1D carbon catalysts for oxygen reduction reactions (ORR) are viable candidates in lieu of platinum‐based catalysts. Hierarchical porous Fe‐N‐doped carbon nanofibers (Fe‐NHCFs) are fabricated via carbonization of MOF nanofibers with a specific surface area of 294 m2 g−1 and inherent hierarchical porosity. Benefiting from the Fe‐N doping‐induced active sites, unique hierarchical porosity, and 1D honeycomb conductive networks to facilitate electron transfer, the freestandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…As shown in Figure , pearl necklace fiber (Zn/Fe ZIF–polyacrylonitrile [PAN]) was first fabricated via coelectrospinning, followed by carbonization–phosphidation to give rise to Fe–P/NHCF. Zn/Fe ZIF nanocrystals showed dodecahedral shape with the size of around 200 nm (Figure a) . Due to the precise optimization of ZIF/PAN ratio, solution viscosity, and electrospinning conditions, ZIF nanocrystals were uniformly distributed in the fibrous strings, portraying the necklace structure (Figure b and Figure S1e, Supporting Information) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure , pearl necklace fiber (Zn/Fe ZIF–polyacrylonitrile [PAN]) was first fabricated via coelectrospinning, followed by carbonization–phosphidation to give rise to Fe–P/NHCF. Zn/Fe ZIF nanocrystals showed dodecahedral shape with the size of around 200 nm (Figure a) . Due to the precise optimization of ZIF/PAN ratio, solution viscosity, and electrospinning conditions, ZIF nanocrystals were uniformly distributed in the fibrous strings, portraying the necklace structure (Figure b and Figure S1e, Supporting Information) .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, NCF was obtained following the same procedure except for the absence of ZIF. For synthesizing Fe–P/NHCF or N/PHCF, 1.0 g of sodium hypophosphite monohydrate was put at the upstream site while 100 mg of Fe–NHCF or NHCF at the downstream in the tubular furnace, which were heated at 300 °C for 2 h under flowing argon …”
Section: Methodsmentioning
confidence: 99%
“…[ 90 ] The metal‐organic framework (MOF) materials can be used as another ideal precursors to prepare the air catalysts with abundant M–N–C active sites. [ 91–97 ] For example, the ZIF‐67 derived Co/N–C particles on the PAN‐based carbon nanofibers (C‐PAN@ZIF‐67) with gems‐on‐string structure and more Co–N–C active sites exposure, which exhibit a long‐term stability of 965 h ( j = 10 mA cm −2 , 10 min per cycle) (Figure 8d). [ 98 ] Similarly, bimetallic Zn/Co–ZIF was used to synthesize the CNF@Zn/CoNC.…”
Section: Electrospinning In Zabsmentioning
confidence: 99%
“…The Co/CoO X -N-C exhibited excellent discharge specific capacity (610 mAh g −1 ) and discharge voltage, which are comparable to 20 wt % Pt/C and RuO 2 . Moreover, Wu et al have reported that hierarchical porous Fe-N-doped carbon nanofibers (Fe-NHCFs) can be fabricated via carbonization of MOF nanofibers [98]. Fe-N doping induces a large number of active sites to enhance the electrocatalytic activity of materials.…”
Section: Electrospun Mofs-derived Carbon Nanofibersmentioning
confidence: 99%